The future of Extracellular Vesicles as Theranostics – an ISEV meeting report. Issue 1 (4th September 2020) - Soekmadji, Carolina; Li, Bo; Huang, Yiyao; Wang, Haifang; An, Taixue; Liu, Chunchen; Pan, Weilun; Chen, Jing; Cheung, Lesley; Falcon‐Perez, Juan Manuel; Gho, Yong Song; Holthofer, Harry B.; et al.
ABSTRACT: The utilization of extracellular vesicles (EVs) in clinical theranostics has rapidly advanced in the past decade. In November 2018, the International Society for Extracellular Vesicles (ISEV) held a workshop on "EVs in Clinical Theranostic". Here, we report the conclusions of roundtable discussions on the current advancement in the analysis technologies and we provide some guidelines to researchers in the field to consider the use of EVs in clinical application. The main challenges and the requirements for EV separation and characterization strategies, quality control and clinical investigation were discussed to promote the application of EVs in future clinical studies.